Mapping Soil Surface Macropores Using Infrared Thermography: An Exploratory Laboratory Study - João L. M. P. de Lima; João R. C. B. Abrantes; Valdemir P. Silva; M. Isabel P. de Lima; Abelardo A. A. Montenegro (The Scientific World Journal)
Macropores and water flow in soils and substrates are complex and are related to topics like preferential flow, nonequilibrium flow, and dual-continuum. Hence, the quantification of the number of macropores and the determination of their geometry are expected to provide a better understanding on the effects of pores on the soil’s physical and hydraulic properties. This exploratory study aimed at evaluating the potential of using infrared thermography for mapping macroporosity at the soil surface and estimating the number and size of such macropores. The presented technique was applied to a small scale study (laboratory soil flume).